Dispersive viscosurgical devices demonstrate greater efficacy in protecting corneal endothelium in vitro - Yildirim, Timur Mert; Auffarth, Gerd U.; Son, Hyeck Soo; Khoramnia, Ramin; Munro, Donald John; Merz, Patrick (BMJ open ophthalmology, 2019)
Objective During phacoemulsification, the corneal endothelium is protected by an ophthalmic viscosurgical device (OVD). In this in vitro study, we assessed six different OVDs for their effectiveness in protecting the corneal endothelium. - Methods and analysis Phacoemulsification was performed in cadaver eyes of young pigs. Five syringe units of six different OVDs were tested (Healon EndoCoat, Viscoat, Methylvisc, Healon, Healon GV, ProVisc). After surgery, the area of endothelium coated with OVD was determined in relation to the total endothelial surface. Additionally, an endothelial cell count was obtained. As a control, an endothelial cell count was obtained from freshly trephined corneas. Statistical analysis was performed using the Mann-Whitney U test and the Spearman correlation. - Results The least postoperative endothelial coating and cell count were observed in the cohesive OVDs while the dispersive OVDs showed statistically significant higher values. Healon EndoCoat and Viscoat yielded a coating area of 86 (85-92)% and 85 (85-90)%, respectively. Endothelial cell count was highest in the two dispersive groups with 4065 (3928-4088) cells/mm2 (Methylvisc) and 4032 (4015-4115) cells/mm2 (Viscoat). Endothelial coating area and endothelial cell count correlated statistically significantly. - Conclusion Dispersive OVDs from this study showed greater adherence to the endothelial surface than the cohesive ones. Furthermore, postoperative endothelial cell counts of corneas treated with dispersive OVDs were higher than of corneas treated with cohesive OVDs. Our in vitro results suggest that dispersive OVDs protect the corneal endothelium better during phacoemulsification than cohesive OVDs.